(untitled) (Panacea Journal of Medical Sciences, 2024)
Aim: To evaluate the changes in HRCT temporal bone in patients having Chronic otitis media - squamosal type. Materials and Methods : A total of 60 patients diagnosed as having squamosal type chronic otitis media were assessed on the basis of clinical history, examination under microscope and otoscopic examination findings. An HRCT was performed to examine the location and size of the cholesteatoma, the progression of the pathology in the middle ear and antrum, the status of the ossicular chains, the scutum, the health of the facial nerve, the tegmen plate, and the progression of diseases outside the middle ear. Results: Of 60 patients, males were more commonly affected with decreased hearing sensitivity being the most common complaint. Ossicular erosion was the commonest finding in HRCT temporal bone. HRCT helps in assessing the changes in temporal bone in patients of Chronic Otitis Media Squamosal and correlating them with clinical findings. Conclusions: HRCT Temporal bone is a common modality available in diagnosing and knowing the extent of the disease, and can inform the clinician of its extent, severity, and associated pathologies.